2007
DOI: 10.1021/jp070101k
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Substituted Side Group on the Molecular Structure and Electronic Properties of TPP and Related Implications on Organic Zeolites Use

Abstract: Tris(o-phenylenedioxy)cyclotriphosphazene (TPP) became a compound of choice to investigate the structural features of organic zeolite and their potential applications. Different TPP-like materials are studied in this Letter from the electron-donor (E-D) capacity viewpoint, since this was reported as a stabilizing parameter of the TPP-Lewis acid inclusion compound up to high temperatures. On the basis of DFT-PBE0/6-31G(d,p) calculations, the results reported herein show a tight dependence of the E-D of the enti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…This is even the case for TPP/benzene IC, in which the shape of guest molecules is simple and highly symmetric [16,17,18,19,20]. In addition, TPP is also a medium for gas storage because the strong affinity of the wall of the nanochannels makes it possible to include even gas molecules [21,22,23]. …”
Section: Introductionmentioning
confidence: 99%
“…This is even the case for TPP/benzene IC, in which the shape of guest molecules is simple and highly symmetric [16,17,18,19,20]. In addition, TPP is also a medium for gas storage because the strong affinity of the wall of the nanochannels makes it possible to include even gas molecules [21,22,23]. …”
Section: Introductionmentioning
confidence: 99%
“…Our preliminary calculations have proved that based on Koopman`s theory, the HF/6-311+G* can yield an excellent accuracy for adiabatic IP [16]. …”
Section: Computational Strategymentioning
confidence: 76%
“…We focused our interest on the relationship between the E-D capacity of the side fragment (part C), bridge (part B), and that for the entire molecule. Although a number of theoretical works on phosphazene containing systems can be found in the literature [15,16], very few were devoted to related OZ and the relationship between E-D and the structure of molecules [16]. This contribution may provide some helpful insights toward the understanding of TPP-like OZ uses and the further design as well.…”
Section: Introductionmentioning
confidence: 99%
“…Spirocyclic phosphazenes are of particular interest because of their ability to act as host molecules,9 as well as to induce inclusion polymerization 10. Recent calculations on tris( o ‐phenylenedioxy)cyclotriphosphazene and related cycles have shown that the electron‐donating capacity of the entire molecule is very dependent on that of the side‐group11 and that good electron‐donating capacity and the paddle wheel molecular shape make them good candidates for organic superconductors 12…”
Section: Introductionmentioning
confidence: 99%